A Retrospective Study of Ruminant Cases Presented Between 1996 and 2005 at the Veterinary Teaching Hospital, University Of Ibadan, Ibadan, Nigeria (2016)
Retrospective study of ruminant cases (cattle, sheep and goats) presented to the Veterinary Teaching Hospital, University of Ibadan, Ibadan between a period of ten years (January1996 to December 2005) was conducted to determine the most prevalent diseases using clinical case file records. Within the period of study, a total of 601 cases were handled out of which 394 (65.56%) occurred in goats, 171(28.45 %) sheep and 36(5.99%) cattle. The most prevalent infections in the three species were ectoparasitism (31.11%), endoparasitism (16.97%) and reproductive cases (13.31%). Among caprine species, endoparasitism was 27.16%, while ectoparasitism and reproductive conditions had 20.96% and 13.96% respectively. As for ovine species endoparasitism was 38.01% while ectoparasitism 9.94% and reproductive conditions had 9.94. But among bovine species, endoparasitism was 41.67%, reproductive conditions had 22.22% and bacterial diseases had 16.67%. The high prevalence of these conditions may be due to poor management practices, improper health/veterinary care, stress on pregnant animals, and neglect of prophylactic measures for disease prevention. There is therefore need for awareness and education of livestock farmers/owners on effective prevention and control measures through livestock extension services and proper management system that restrict animals from roaming freely thereby preventing injuries caused by trauma.